Penanganan Fisioterapi pada Kasus PPOK - Amalia Ferina Anggraeni; Adnan Faris Naufal; Mulatsih Nita Utami (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
COPD is a condition characterized by airflow obstruction that cannot be completely corrected. This limitation generally worsens over time and is associated with abnormal permeability to noxious particles or gases, resulting in narrowing of the airways, increased mucus secretion, and changes in the vascular system. The increase in chest expansion capacity is caused by the activity of respiratory muscle contraction. The activity of the respiratory muscles plays a role in chest expansion, which also affects lung growth. It is stated that the strength of the respiratory muscles decreases with age. Loss of intercostal muscle mass and strength are factors that reduce the ability of chest wall presence or development. This study used a case report design research method. Physiotherapy management for COPD is increasingly focused on exercise-based rehabilitation, both in outpatient and inpatient settings. Some therapies such as breathing exercises, thoracic expansion exercises and muscle release.